Firm Formation with Complementarities: The Role of the Entrepreneur - Christian Roessler; Philipp Koellinger (Tinbergen Institute, 2009)
We model entrepreneurship and the emergence of firms as a result of simultaneous bidding for labor services among heterogeneousagents. Unique to our approach is that occupational choices, jobmatching and organizational forms are determined simultaneously, sothat the opportunity costs of entrepreneurs are accounted for. Wefind that (1) individuals who are relatively unmanageable become entrepreneurs; (2) entrepreneurs compete against each other and createvalue by building efficient organizations and offering potentially verywell paid jobs for others; and (3) entry of an additional entrepreneurtypically reduces some individual wages, but always raises the averagewage and depresses the average incomes of incumbent entrepreneurs- strictly so if the new firm partially imitates existing organizations.Our results shed a new light on the role of entrepreneurs in the economy and may be applied to explain low returns to self-employment.
Keywords: L26; J24; J31; D20; L23; 330; Entrepreneurship; job matching; occupational choice; firm formation; firm organization; Unternehmensgründung; Arbeitsnachfrage; Substitutionselastizität; Unternehmensorganisation; Entrepreneurship-Ansatz; Spieltheorie